2010
DOI: 10.1007/s10815-010-9427-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mullerian hormone and cumulative pregnancy outcome in in-vitro fertilization

Abstract: Purpose To evaluate the role of Anti-mullerian hormone (AMH) in predicting cumulative pregnancy outcome during in-vitro fertilization (IVF) treatment. Methods Serum AMH levels on day 6 of ovarian stimulation were taken from 180 women undergoing IVF with or without intracytoplasmic sperm injection (ICSI). The main outcome measures were ongoing pregnancy in the fresh cycle, cumulative ongoing pregnancy and ovarian response.Results There was a trend of higher median AMH levels in subjects achieving ongoing pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
1
20
0
2
Order By: Relevance
“…With the recent advent of embryo cryopreservation technology, F-TET cycles have become an integral part of IVF, reducing the incidence of early onset OHSS (13,14). However, there have been few reports on the relationship between pregnancy rate and single-blastocyst evaluation in F-TET cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the recent advent of embryo cryopreservation technology, F-TET cycles have become an integral part of IVF, reducing the incidence of early onset OHSS (13,14). However, there have been few reports on the relationship between pregnancy rate and single-blastocyst evaluation in F-TET cycles.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent advent of embryo cryopreservation technology, which has led to a surplus of good quality embryos in a considerable proportion of IVF cycles and has diminished the incidence of ovarian hyperstimulation syndrome (OHSS), frozen-thawed embryo transfer (F-TET) cycles have become an integral part of IVF treatment (13,14). Moreover, although endometrial receptivity reportedly differs significantly between fresh embryo transfer (FET) and F-TET cycles (15), there has been only one report on the relationship between single blastocyst quality and pregnancy rates in F-TET cycles (10).…”
mentioning
confidence: 99%
“…Our findings substantiate the significant predictive ability of serum AMH for pregnancy rates, as have many recent studies. [12][13][14][15][16][17][18][19][20] The predictive ability of AMH for pregnancy rates remained significant when we stratified serum AΜH in quartiles. Compared with the first quartile of AMH levels, we found a 5-fold increase in odds of pregnancy in the second quartile, an 8-fold in the third quartile and a 30-fold in the fourth quartile.…”
Section: Resultsmentioning
confidence: 96%
“…11 Indeed, a large number of studies have reported a positive correlation between AMH and pregnancy rates. [12][13][14][15][16][17][18][19][20] However, there are also a number of studies showing limited predictive ability or no correlation between AMH levels and IVF outcome. 4,7,[21][22][23][24][25] The importance of such predictive ability is greater in women of advanced reproductive age due to the reduced success rates of this population.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who returned to the Centre for treatment underwent frozen-thaw cycles using their cryopreserved embryos as previously described by Kini et al [19]. Patients who are cycling underwent down-regulation with GnRH agonists (Buserelin) for 2 weeks until the endometrial thickness was 4 mm or less on ultrasound or E2 levels < of 150pmol/l or less.…”
Section: Frozen-thaw Cyclesmentioning
confidence: 99%